2007
DOI: 10.1200/jco.2006.09.3849
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ixabepilone (BMS-247550) in a Phase II Study of Patients With Advanced Breast Cancer Resistant to an Anthracycline, a Taxane, and Capecitabine

Abstract: Ixabepilone demonstrated clear activity and a manageable safety profile in patients with MBC resistant to anthracycline, taxane, and capecitabine. Responses were durable and notable in patients who had not previously responded to multiple prior therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
243
1
12

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 365 publications
(270 citation statements)
references
References 19 publications
14
243
1
12
Order By: Relevance
“…A phase 2 trial in patients with MBC resistant to an anthracycline, a taxane, and capecitabine showed a response rate of 12% with stabilization of disease in an additional 50% of patients (54). Ixabepilone treatment led to durable responses in this highly chemo-resistant patient population, even in patients who had not responded to multiple previous therapies (54). Consistent with these results, a 12% response rate was reported in a phase 2 trial in patients with taxaneresistant MBC (55).…”
Section: Epothilone B Analog Ixabepilonesupporting
confidence: 71%
See 1 more Smart Citation
“…A phase 2 trial in patients with MBC resistant to an anthracycline, a taxane, and capecitabine showed a response rate of 12% with stabilization of disease in an additional 50% of patients (54). Ixabepilone treatment led to durable responses in this highly chemo-resistant patient population, even in patients who had not responded to multiple previous therapies (54). Consistent with these results, a 12% response rate was reported in a phase 2 trial in patients with taxaneresistant MBC (55).…”
Section: Epothilone B Analog Ixabepilonesupporting
confidence: 71%
“…Clinical activity of ixabepilone has also been reported in other tumor types including prostate, renal, NSCLC, and pancreatic cancers (38). A phase 2 trial in patients with MBC resistant to an anthracycline, a taxane, and capecitabine showed a response rate of 12% with stabilization of disease in an additional 50% of patients (54). Ixabepilone treatment led to durable responses in this highly chemo-resistant patient population, even in patients who had not responded to multiple previous therapies (54).…”
Section: Epothilone B Analog Ixabepilonementioning
confidence: 99%
“…This may have selected a patient population less likely to experience neuropathy. Nevertheless, neuropathy was comparable to that seen in breast cancer studies [9][10][11][12][13] in which 12% to 20% of patients develop grade 3 neurotoxicity.…”
Section: Discussionsupporting
confidence: 76%
“…Accelerated approval is granted based on the surrogate end points that are less well established but reasonably likely to predict a longer or a better life. During the past decade, new agents that have been approved include the selective estrogen receptor downregulator fulvestrant for HR-positive disease [110,111] and cytotoxic agents such as nab-paclitaxel [112], gemcitabine combined with paclitaxel for the first-line therapy [113], capecitabine for anthracycline and taxane-resistant disease [114,115], and ixabepilone alone [116] or plus capecitabine for anthracycline and taxane-resistant disease (Table 3) [117]. Biologic agents that have been approved include trastuzumab combined with paclitaxel or used alone for HER2-positive disease [67,118], lapatinib, a tyrosine kinase inhibitor, combined with capecitabine for trastuzumab-refractory HER2-positive disease [73], and bevacizumab plus paclitaxel for the first-line therapy of Her2/neu negative disease [76].…”
Section: Regulatory Approval Of New Agentsmentioning
confidence: 99%